Developments in the Histopathological Classification of ANCA-Associated Glomerulonephritis - van Daalen, Emma E; Wester Trejo, Maria A C; Göçeroğlu, Arda; Ferrario, Franco; Joh, Kensuke; Noël, Laure-Hélène; Ogawa, Yayoi; Wilhelmus, Suzanne; Ball, Miriam J; Honsova, Eva; Hruskova, Zdenka; Kain, Renate; et al. (Clinical journal of the American Society of Nephrology, 2020)
BACKGROUND AND OBJECTIVES: The histopathologic classification for ANCA-associated GN distinguishes four classes on the basis of patterns of injury. In the original validation study, these classes were ordered by severity of kidney function loss as follows: focal, crescentic, mixed, and sclerotic. Subsequent validation studies disagreed on outcomes in the crescentic and mixed classes. This study, driven by the original investigators, provides several analyses in order to determine the current position of the histopathologic classification of ANCA-associated GN. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: A validation study was performed with newly collected data from 145 patients from ten centers worldwide, including an analysis of interobserver agreement on the histopathologic evaluation of the kidney biopsies. This study also included a meta-analysis on previous validation studies and a validation of the recently proposed ANCA kidney risk score. RESULTS: The validation study showed that kidney failure at 10-year follow-up was significantly different between the histopathologic classes (P<0.001). Kidney failure at 10-year follow-up was 14% in the crescentic class versus 20% in the mixed class (P=0.98). In the meta-analysis, no significant difference in kidney failure was also observed when crescentic class was compared with mixed class (relative risk, 1.15; 95% confidence interval, 0.94 to 1.41). When we applied the ANCA kidney risk score to our cohort, kidney survival at 3 years was 100%, 96%, and 77% in the low-, medium-, and high-risk groups, respectively (P<0.001). These survival percentages are higher compared with the percentages in the original study. CONCLUSIONS: The crescentic and mixed classes seem to have a similar prognosis, also after adjusting for differences in patient populations, treatment, and interobserver agreement. However, at this stage, we are not inclined to merge the crescentic and mixed classes because the reported confidence intervals do not exclude important differences in prognosis and because an important histopathologic distinction would be lost.
Keywords: renální insuficience; Biopsy; Humans; lidé středního věku; Disease Progression; glomerulonephritis; Predictive Value of Tests; Confidence Intervals; ledviny; Female; rizikové faktory; Aged; kidney biopsy; protilátky proti cytoplazmě neutrofilů; Kidney; senioři; lidé; reprodukovatelnost výsledků; biopsie; časové faktory; Cohort Studies; Glomerulonephritis; Antineutrophil Cytoplasmic; glomerulonefritida; ženské pohlaví; Renal Insufficiency; Male; Reproducibility of Results; Middle Aged; prediktivní hodnota testů; Retrospective Studies; Antibodies, Antineutrophil Cytoplasmic; prognóza; ANCA; Antibodies; progrese nemoci; retrospektivní studie; Observer Variation; mužské pohlaví; Time Factors; Prognosis; Risk Factors